Export Import Theory Practices And Procedures - Seyoum, Belay (New York Routledge, 2022)
"This book remains the sole export-import textbook aimed squarely at the academic audience. Discussing theoretical issues in depth, while maintaining a practical approach, it offers a comprehensive exploration of import procedures and export regulations. In addition to updated cases, this new edition includes: New major developments in bilateral and regional trade agreements Changes to INCOTERMS 2010 Coverage of the role of e-commerce Expanded updates on methods of payment, export pricing and government export finance This clearly written and comprehensive textbook will ground students in theory and prepare them for the realities of a career in this fast-moving field. Suitable for upper-level undergraduates and postgraduates of international trade, the book stands alone in its blend of conceptual frameworks and cogent analysis. A related website, filled with export-import resources, opinion pieces, cases, and the latest news is located at: www.export-importtradecenter.com"--
Includes bibliographical references and index.
Keywords: Exports; Imports; Export marketing; International trade